The complete chloroplast genome of Petasites japonicus (Siebold & Zucc.) Maxim. (Asteraceae). Issue 12 (2nd December 2021) - Hashimoto, Tamaki; Tsubota, Hiromi; Shimamura, Masaki; Inoue, Yuya
Abstract: The complete chloroplast (cp) genome sequence of Petasites japonicus (Asteraceae) was determined. The cp genome is 150, 445 bp and consists of a large single-copy region (82, 910 bp), a small single-copy region (17, 907 bp), and a pair of inverted repeats (24, 814 bp). It encodes a set of 114 genes, consisting of 80 protein-coding genes, 30 tRNA genes, and four rRNA genes. Phylogenetic inference confirmed that P. japonicus is sister to the genus Ligularia in the tribe Senecioneae of Asteraceae.